2023
DOI: 10.3390/nu15010214
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Sugar-Sweetened Beverages and Male Pattern Hair Loss in Young Men

Abstract: We performed this study to investigate the association between sugar-sweetened beverage (SSB) consumption and male pattern hair loss (MPHL) in young men. We conducted this cross-sectional study from January to April 2022 in mainland China. Young people aged 18–45 years (n = 1951) were recruited from 31 provinces in China. We used a self-reported online survey for data collection. We explored the associations between the amount/frequency of SSB consumption and MPHL by using a binary logistic regression model, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…High sugar intake impacts hair loss by activating the polyol pathways [ 48 , 49 , 50 ]. A recent study revealed that consuming sugar-sweetened beverages is linked with a high risk of male pattern hair loss in young men [ 51 ].…”
Section: Factors Affecting Hair Healthmentioning
confidence: 99%
“…High sugar intake impacts hair loss by activating the polyol pathways [ 48 , 49 , 50 ]. A recent study revealed that consuming sugar-sweetened beverages is linked with a high risk of male pattern hair loss in young men [ 51 ].…”
Section: Factors Affecting Hair Healthmentioning
confidence: 99%
“…The role of biochemical parameters in the development of alopecia has been reported [12,[14][15][16]. The prevalence of non-cicatricial alopecia continues to increase due to unfavorable changes in patient lifestyle, nutrition, and cosmetic habits, as well as hormonal disbalance or psychological stress [14].…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al [12] reported that the consumption of sugar-sweetened beverages was associated with an elevated risk of hair loss in young men. Alopecia has been known to be linked with glucose metabolism, and high sugar intake may play a role in hair loss by activating the polyol pathways [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations